2006
DOI: 10.1002/bse.524
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability: Consumer Perceptions and Marketing Strategies

Abstract: This is an author produced version of a paper published in Business Strategy and the Environment (ISSN 0964-4733, eISSN 1099-0836) This version may not include final proof corrections and does not include published layout or pagination. Citation Details"This is the peer reviewed version of the following article: MCDONALD, S. and OATES, C. J., 2006. Sustainability: consumer perceptions and marketing strategies. Business Strategy and the Environment, 15 (3), pp. 157-170, which has been published in final fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
126
0
9

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(139 citation statements)
references
References 17 publications
4
126
0
9
Order By: Relevance
“…However, this was shown to be implemented on an operational level by improving efficiency in linear packaging end-of-life fates (such as reducing post-consumer waste). This was described as "low-hanging fruit" by the Hotel interview participants, which aligns with the description of a "cherry picker" by McDonald and Oates (2006) [71], or what Alakeson and Sherwin (2004) [72], Lucas (2010) [73], and Petala et al (2010) [48] describe as an "ad hoc approach" Disruptive or innovative sustainable development efforts are not identified in this research. This also holds for companies that claim sustainability to be holistically embedded in their identity and branding.…”
Section: Strategic and Operational Sustainabilitysupporting
confidence: 74%
“…However, this was shown to be implemented on an operational level by improving efficiency in linear packaging end-of-life fates (such as reducing post-consumer waste). This was described as "low-hanging fruit" by the Hotel interview participants, which aligns with the description of a "cherry picker" by McDonald and Oates (2006) [71], or what Alakeson and Sherwin (2004) [72], Lucas (2010) [73], and Petala et al (2010) [48] describe as an "ad hoc approach" Disruptive or innovative sustainable development efforts are not identified in this research. This also holds for companies that claim sustainability to be holistically embedded in their identity and branding.…”
Section: Strategic and Operational Sustainabilitysupporting
confidence: 74%
“…For example, in relation to recycling, Brook Lyndhurst [66] reported that convenience is related to kerbside recycling service provision, distance from bring banks and their location in terms of everyday trips, availability of a car, and also issues of time and storage space. McDonald and Oates [115] drew a parallel between the concept of convenience in relation to recycling and Peattie's [95] concept of compromise in relation to green consumerism. The aspects of compromise include paying a premium for a green product, sacrificing product performance for environmental benefits, and having to obtain goods from non-standard outlets.…”
Section: Determining Factorsmentioning
confidence: 99%
“…Thus, lifestyle can be viewed as an interpretive framework for the construction of social reality (Yeh and Chen 2011). Upon acquiring explicit knowledge of how specific activities affect society (Buenstorf and Cordes 2008), consumers likely pursue behavior participations such as consuming green products, recycling, considering clothing care, and adopting eco-friendly behavior (McDonald and Oates 2006). For instance, sustainable lifestyle societies, such as LOHAS, Good Neighbors, Tree Huggers, and Eco-Village, are actively engaged in a broad range of practices based on environmental considerations and seek to make these considerations apply as legitimate rules within the society (Spaargaren 2003).…”
Section: Sustainable Lifestyle Practicesmentioning
confidence: 99%